Ingredients in functional confectionery - Bohun, Vladimir (My University, 2014)
There is a strong trend in confectionery towards functional products. The explosion of functional products is due to many factors, but particularly the influence of nutritionists on the consumer, and a better understanding of the benefits, either real or perceived, of nutritional additives — antioxidants, vitamins, herbs and the balance of carbohydrates, proteins and fats in our diet.
Keywords: functional confectionery; functional products; confectionery; функціональні кондитерські вироби; кондитерські вироби; функціональні продукти; функциональные кондитерские изделия; кондитерские изделия; функциональные продукты